Gas Adsorption Mechanism on 2D Materials: The Hyperpolarizability Evolution Analyzed by Nonlinear Optics - Yen, Ting‐Yu; Hung, Yang‐Hao; Lee, Yu‐Zen; Ho, Yen‐Teng; Lan, Yann‐Wen; Wu, Chiu‐Hsien; Hung, Kuan‐Ming; Lo, Kuang Yao (Advanced functional materials, 2024)
While understanding the competitive adsorption behavior of gas sensor is important, it is yet to be unraveled. Especially for the influence of water molecules to the gas adsorbed on 2D materials. This study explores the potential of layered 2D materials as a candidate material for gas sensing, employing non‐destructive measurement, and second harmonic generation (SHG). The investigation focuses on analyzing oxygen, ammonia, and water vapor adsorbed on a WS2 surface by studying the evolutions in electric dipole and electric field. Leveraging the simplified bond hyperpolarizability model (SBHM), a foundation is established for gas sensors utilizing high‐quality 2D materials. This approach facilitates the detection of material modifications in response to environmental influences, including the inevitable water molecules. The obtained hyperpolarizability from SBHM exhibits remarkable consistency with Langmuir's adsorption model, confirming the physical adsorption in the system. In addition, the competitive effects between gases are explored by comparing experimental results with theoretical predictions based on Boltzmann distribution and density functional theory (DFT) calculations. This highlights the effectiveness of SHG and SBHM in studying gas adsorption on layered van der Waals materials. This study assesses the potential of layered 2D materials for gas sensing using second harmonic generation (SHG). It focuses on the adsorption behaviors of oxygen, ammonia, and water vapor on WS2 surfaces. By applying the simplified bond hyperpolarizability model, it confirms physical adsorption and explores competitive interactions between gases, aligning with Langmuir's model and theoretical predictions from density functional theory.